Mechanisms and Product Options of Magnesiothermic Reduction of Silica to Silicon for Lithium-Ion Battery Applications - Tan, Yu; Jiang, Tingting; Chen, George Z. (Frontiers in Energy Research, 2021)
Lithium-ion batteries (LIBs) have been one of the most predominant rechargeable power sources due to their high energy/power density and long cycle life. As one of the most promising candidates for the new generation negative electrode materials in LIBs, silicon has the advantages of high specific capacity, a lithiation potential range close to that of lithium deposition, and rich abundance in the earth's crust. However, the commercial use of silicon in LIBs is still limited by the short cycle life and poor rate performance due to the severe volume change during Li+ insertion/extraction, as well as the unsatisfactory conduction of electron and Li+ through silicon matrix. Therefore, many efforts have been made to control and stabilise the structures of silicon. Magnesiothermic reduction has been extensively demonstrated as a promising process for making porous silicon with micro- or nanosized structures for better electrochemical performance in LIBs. This article provides a brief but critical overview of magnesiothermic reduction under various conditions in several aspects, including the thermodynamics and mechanism of the reaction, the influences of the precursor and reaction conditions on the dynamics of the reduction, and the interface control and its effect on the morphology as well as the final performance of the silicon. These outcomes will bring about a clearer vision and better understanding on the production of silicon by magnesiothermic reduction for LIBs application.